KAJAN DINAMIKA TATA GUNA LAHAN PADA KAWASAN SEKITAR PUSAT PELAYANAN KOTA MANADO - Rogi, Octavianus H. A.; Tilaar, Sonny; Makarau, Vicky H.; Malik, Andi A. M.; Moniaga, Ingerid (MEDIA MATRASAIN, 2011)
ABSTRACTThis study aims to determine the dynamics change of the land use pattern in the region around the service center of Manado city. Moreover, this study also aims to determine what factors are influencing changes in land use of the area.Theoretical studies indicate that the land use of a city can be present in a concentric pattern (single center), sectoral or multiple centered. Changes in land use patterns in urban areas occurs dynamically and is influenced by human factors, physical factors and the factor of urban landscapes. Changes in the structure of land use include the changes of development, location and the behavior setting.The major service center area of Manado is the old downtown area and the reclamation area along the Piere Tendean street. To that end, research locations specified in the administrative area of South Wenang and South Titiwungen flanked by Piere Tendean street (Boulevard) and Sam Ratulangi street.The study was conducted for 6 (six) months. The data used in this study includes primary and secondary data. Primary data include (a) the information from questionnaires distributed to 100 respondents who represent the element of local area residents informing about the aspects of their perceptional view of the economic value of land and land use patterns in which they live, and (b) information of land characteristics, including the physical condition of landscapes, availability of infrastructure, and so on, which obtained through field observations. Secondary data include the results of the institutional surveys through sources relevant to the topic under study. Respondents were taken with a purposive sampling method by an amount proportional to the number based on the sub-region. The analytical technique in this research is Descriptive Analysis, which analyzes the state of the object directly to the study through the description, understanding, or better explanations to the measurable variables or unmeasureable ones.In conclusion, the results of the study were (1) land use changes in the study area occurred in three periods, namely before the reclamation, after the reclamation and present days; ((2) changes that occur mainly is the transition of the settlements area into trading and services area gradually, following the path of primary and secondary roads, and (3) land use changes in the area of research primarily influenced by the strategic location of the sites, which is near the service center of the city, with high economic value of land.Key words: land use, service center area, descriptive analysis